2018
DOI: 10.1002/ehf2.12376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bromocriptine on left ventricular functional recovery in peripartum cardiomyopathy: insights from the BRO‐HF retrospective cohort study

Abstract: AimsBromocriptine is thought to facilitate left ventricular (LV) recovery in peripartum cardiomyopathy (PPCM) through inhibition of prolactin secretion. However, this potential therapeutic effect remains controversial and was incompletely studied in diverse populations.Methods and resultsConsecutive women with new‐onset PPCM (n = 76) between 1994 and 2015 in Quebec, Canada, were classified according to treatment (n = 8, 11%) vs. no treatment (n = 68, 89%) with bromocriptine. We assessed LV functional recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Both high and low doses were associated with low mortality (there was no placebo arm). A Canadian study reported a greater LV recovery in PPCM patients treated with bromocriptine . Treatment with bromocriptine may especially be considered in patients with right ventricular involvement .…”
Section: Managementmentioning
confidence: 99%
“…Both high and low doses were associated with low mortality (there was no placebo arm). A Canadian study reported a greater LV recovery in PPCM patients treated with bromocriptine . Treatment with bromocriptine may especially be considered in patients with right ventricular involvement .…”
Section: Managementmentioning
confidence: 99%
“…По мнению M. TremblayGravel и соавт., использова ние бромокриптина в начальном периоде болезни может ограничить степень повреждения, если во главу поста вить необходимость ингибирования пролактина [12].…”
Section: Discussionunclassified
“… 123 A protein resulting from cleavage of the lactation hormone prolactin, 16-kilodalton, has anti-angiogenic properties, and has been linked to myocyte damage and HF in animal models. 124 Higher LV end diastolic diameter, low LVEF on presentation, and African American ethnicity have been associated with poor LV recovery. 125 In addition to standard HF goal-directed medical therapy, bromocriptine, an antagonist of prolactin production in the anterior hypothalamus, might be useful in improving LVEF and clinical outcomes at follow-up.…”
Section: Pathophysiologymentioning
confidence: 99%
“…125 In addition to standard HF goal-directed medical therapy, bromocriptine, an antagonist of prolactin production in the anterior hypothalamus, might be useful in improving LVEF and clinical outcomes at follow-up. 121 , 124 Anticoagulation is recommended in conjunction with bromocriptine, and might be considered in women with PPCM and very low LVEF. 121 Pregnancy after a diagnosis of PPCM should be avoided in women with any residual LV impairment (LVEF ≤ 50%-55%).…”
Section: Pathophysiologymentioning
confidence: 99%